2019
DOI: 10.1002/jat.3880
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals, antioxidants, nuclear factor‐E2‐related factor‐2 and liver damage

Abstract: Oxidative/nitrosative stress is proposed to be a critical factor in various diseases, including liver pathologies. Antioxidants derived from medicinal plants have been studied extensively and are relevant to many illnesses, including liver diseases. Several hepatic disorders, such as viral hepatitis and alcoholic or nonalcoholic steatohepatitis, involve free radicals/oxidative stress as agents that cause or at least exacerbate liver injury, which can result in chronic liver diseases, such as liver fibrosis, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 234 publications
0
59
0
Order By: Relevance
“…[47] Thus, the overall hepatoprotective pharmacology of omaveloxolone and its analogs are consistent with the profound hepatoprotective properties of Nrf2, which has been studied and reviewed extensively. [21,[48][49][50][51][52] In conclusion, omaveloxolone and TX63682 demonstrated significant hepatoprotection in a rodent model of NASH. Such hepatoprotection was observed in conjunction with improvements in glucose control and lipid handling, which is consistent with the overall phenotype of improved mitochondrial function that is associated with Nrf2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…[47] Thus, the overall hepatoprotective pharmacology of omaveloxolone and its analogs are consistent with the profound hepatoprotective properties of Nrf2, which has been studied and reviewed extensively. [21,[48][49][50][51][52] In conclusion, omaveloxolone and TX63682 demonstrated significant hepatoprotection in a rodent model of NASH. Such hepatoprotection was observed in conjunction with improvements in glucose control and lipid handling, which is consistent with the overall phenotype of improved mitochondrial function that is associated with Nrf2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Several antioxidants have been studied with respect to ALD, including vitamin E and glutathione. Multiple animal and human models have shown that free radicals and oxidative stress can cause or at least exacerbate liver injury in ALD [150,151]. Vitamin E is a first-line therapy for NASH [152].…”
Section: Antioxidants and Micronutrientsmentioning
confidence: 99%
“…ROS include molecules derived from oxygen reduction, such as molecules or atoms that have unpaired electrons and are unstable and highly reactive because they can react with adjacent molecules subtracting electrons. Oxidative intermediaries can generally be classified into oxygen-centered radicals, such as superoxide radical, hydroxyl radical, and peroxyl radical, and oxygen-centered non-radicals, such as hydrogen peroxide and singlet oxygen [ 9 ]. Production of all these molecules is part of aerobic metabolism in humans, which, in a certain way, is important for some physiological functions such as signal transduction pathways and defense against microorganisms (neutrophils, eosinophils, and macrophages during inflammation), among others [ 10 ].…”
Section: Ros Antioxidant Defenses and Liver Damagementioning
confidence: 99%